Back to the future: The effect of returning family successions on firm performance. (2nd March 2021) - Amore, Mario Daniele; Bennedsen, Morten; Le Breton‐Miller, Isabelle; Miller, Danny
Abstract: Research Summary: We study successions from a non‐family CEO back to a family CEO, which we label "Type‐R" successions. In our sample of 489 Italian family firms experiencing the departure of non‐family CEOs, these successions represent 42% of all cases. Our difference‐in‐differences results indicate that family firms undertaking Type‐R successions experience an 18% superiority in profitability. Exploring the heterogeneity underlying this result, we find that Type‐R successions produce weaker results in contexts that are highly volatile and that rely on innovative inputs before succession. Finally, in studying the drivers of the performance increase, we find that Type‐R successions reduce labor costs and spur efficiency. Collectively, our evidence suggests that Type‐R successions improve performance by leveraging family assets while avoiding dysfunctional nepotism and other parochial family priorities. Managerial Summary: How does CEO succession affect family business performance? In this article, we study an unexplored yet common succession pattern in mature family firms—the appointment of a family member following the tenure of an outside CEO. Surprisingly, we find that when, after a period of professional leadership, a family CEO returns to lead the company; the firm exhibits an 18% advantage in profitability. This result is more prevalent in stable industries, where traditional family assets prove especially valuable. A key takeaway of our study is that family leadership can enhance performance in companies that have already professionalized their governance, and thus have learned to reconcile meritocratic principles with family‐based assets.